The Strategic Culture of Trump’s America NATO Policy: A Neoclassical Realist Approach - Lauro Borges (Panoply Journal)
Systemic imperatives are considered the major shaping factor of domestic intervening variables in neoclassical realism. The present article aims to study how the first shapes which variant of American strategic culture and its subcultures tends to manifest under certain structural conditions, having as object of research the Trump’s Administration NATO policy from 2017 to 2019. It was found that systemic conditions in the strategic environment, as interpreted by Trump’s foreign policy executive, favored the expression of a hardline unilateralist subculture of American strategic culture, heir of the Jacksonian tradition. However, the foreign policy executive as a whole is diverse and tends to vary between hardline unilateralists who aim to make NATO more conditional in terms of burden-sharing and conservative nationalists who reassure allies of US commitments to Europe's collective defense.